MANAJEMEN PROGRAM PEMBELAJARAN KOMPENSATORIS ANAK TUNARUNGU DI SEKOLAH LUAR BIASA NEGERI 2 BANTUL (JURNAL ILMIAH TUT WURI HANDAYANI, 2014)
This study aimed to describe the compensatory learning program management which includes planning, implementation, evaluation of compensatory learning for deaf children that cored in special program the Development Comunication Perception of Sound and Rhythm at Special Education Public School 2 Bantul. This study is a qualitative approach. Research sites in Special Education Public School 2 in Bantul. Collecting data using the technique of participant observation, interviews, and documentation. Extend the validity of the data obtained with triangulation. The data were analyzed using an interactive model of Miles and Hubermen, performed during data collection and after data collected by the reduction of data, verification of data and subsequent conclusions. Llesson planning of special program development communication perception of sounds and rhythms as adequate compensatory program. Implementation learning is quite systematic with reference to the scope of the material, standard and basic competencies. In principle the learning evaluation has been made but has not optimal because it just been emphasis on the evaluation of cognitive and psychomotor aspects. It is recommended to related stakeholder such as school administrators, teachers and the government to improve the quality of services for children with special needs, especially children with hearing impairment.